The Clinical Profile of Cat-Scratch Disease’s Neuro-Ophthalmological Effects - Sanda Jurja; Alina Zorina Stroe; Mihaela Butcaru Pundiche; Silviu Docu Axelerad; Garofita Mateescu; Alexandru Octavian Micu; Raducu Popescu; Antoanela Oltean; Any Docu Axelerad (Brain Sciences, 2022)
Cat-scratch disease is an illness caused by Bartonella henselae that occurs as a result of contact with an infected kitten or dog, such as a bite or scratch. It is more prevalent in children and young adults, as well as immunocompromised individuals. There are limited publications examining the features of CSD in patients. As such, the purpose of this research was to assess the clinical neuro-ophthalmological consequences of CSD reported in the literature. Among the ophthalmologic disorders caused by cat-scratch disease in humans, Parinaud oculoglandular syndrome, uveitis, vitritis, retinitis, retinochoroiditis and optic neuritis are the most prevalent. The neurological disorders caused by cat-scratch disease in humans include encephalopathy, transverse myelitis, radiculitis, and cerebellar ataxia. The current review addresses the neuro-ophthalmological clinical manifestations of cat-scratch disease, as described in papers published over the last four decades (1980–2022). All the data gathered were obtained from PubMed, Medline and Google Scholar. The current descriptive review summarizes the most-often-encountered clinical symptomatology in instances of cat-scratch disease with neurological and ocular invasion. Thus, the purpose of this review is to increase knowledge of cat-scratch disease’s neuro-ophthalmological manifestations.